DOS CONCEITOS FILOSÓFICOS ÀS NOVAS PERSPECTIVAS DA TEORIA SINTÉTICA DA EVOLUÇÃO: DESAFIOS DO ENSINO DA BIOLOGIA EVOLUTIVA NO ENSINO MÉDIO - Rodrigues, Raiany Meirelli dos Anjos (2018)
The Evolution theory is regarded as the core of biology, since the understanding of this science can help in the comprehension of facts in the most different areas in biology. In this sense, this research has by objective to understand the knowledge of high school teachers, in the towns of Alagoa Grande-PB and Areia, about this so important theory. To do this, it has been applied a quiz, in which the Bandin’s methodology was used to categorize the answers. From the results we could see that the majority of the teachers in the last year of high school use the most varied methodologies to teach this subject, not just the textbook. However, although evolutionary biology be a central subject in biology, teachers integrate more with the area of genetics. Furthermore, it has been observed that few teachers truly understand the fundamental concepts behind evolution. When questioned about the difficulties of teach the subject they cite: Students, didactic materials and religious conflicts. As a conclusion we can mention the need of a better formation of the future teachers in the subject in addition to a continued formation of those already in classroom, in such way that they can fill the existing gaps in their formation.